Upaya Meningkatkan Keterampilan Berbicara dengan Menerapkan Metode Sosiodrama (Role Playing) di Kelas V SDN 2 Barejulat - Asih Muliasih (Jurnal Paedagogy, 2019)
The purpose of this study was to improve speaking skills by applying the sociodrama method in Class V SDN 2 Barejulat. This study uses a class action research method consisting of 2 action cycles. Each cycle consists of four stages including planning, implementation, observing the results of actions, and reflection. The subjects of this study were 47 grade V students consisting of 27 male students and 20 female students. Data collection instruments used were tests, observation sheets, and documentation. While the data analysis uses descriptive qualitative and quantitative analysis. The results of this study indicate that the sociodrama method can improve speaking skills in Class V SDN 2 Barejulat. This increase can be seen from the classical completeness obtained in the first cycle that is equal to 70.21% and the second cycle increased to 93.62%. This increase can also be seen from the observations of teacher activities by 13 with a good category in the first cycle and increased to 18 with a very good category in the second cycle. Whereas student activity in cycle I was 45 with active categories, increasing to 67 with very active categories in cycle II. Based on the results of the analysis of cycle I and II obtained an increase in classical completeness of 32.40%.